2013
DOI: 10.1371/journal.pone.0075343
|View full text |Cite|
|
Sign up to set email alerts
|

Proteomic Analysis of Liver in Rats Chronically Exposed to Fluoride

Abstract: Fluoride (F) is a potent anti-cariogenic element, but when ingestion is excessive, systemic toxicity may be observed. This can occur as acute or chronic responses, depending on both the amount of F and the time of exposure. The present study identified the profile of protein expression possibly associated with F-induced chronic hepatotoxicity. Weanling male Wistar rats (three-weeks old) were divided into three groups and treated with drinking water containing 0, 5 or 50 mg/L F for 60 days (n=6/group). At this … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
46
1
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 52 publications
(50 citation statements)
references
References 54 publications
2
46
1
1
Order By: Relevance
“…Interestingly, in the absence of F, the expression levels of L-lactate dehydrogenase A chain and L-lactate dehydrogenase C chain were lower in ND rats than in D rats. A previous study reported the absence of L-lactate dehydrogenase A chain in the liver of rats (ND) treated with F [28]. Decreased expression of this enzyme leads to increased aerobic glycolysis.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Interestingly, in the absence of F, the expression levels of L-lactate dehydrogenase A chain and L-lactate dehydrogenase C chain were lower in ND rats than in D rats. A previous study reported the absence of L-lactate dehydrogenase A chain in the liver of rats (ND) treated with F [28]. Decreased expression of this enzyme leads to increased aerobic glycolysis.…”
Section: Discussionmentioning
confidence: 94%
“…Previous studies have treated the animals with F for 6 weeks [4], [28][30]; however, a pilot study revealed high levels of mortality prior to completion of the experimental period. Therefore, an experimental time of 22 days was selected.…”
Section: Discussionmentioning
confidence: 99%
“…The cDNA was reversed transcription (RT) from 1 μg of total RNA with primer oligo(dT)18 by using superscript II RNase (Reverse Transcriptase; Invitrogen Inc., USA). The caspase-3 and −9 cDNA were amplified by polymerase chain reaction (PCR) based on a previously published rat cDNA primer sequence (6)(7)(8). β-Actin was the internal standard.…”
Section: Immunohistochemistry Studiesmentioning
confidence: 99%
“…Many reports have shown that F can cause progressive degeneration of the structure and functions of skeletal muscles, the brain, and the spine. In addition, it increases the aerobic metabolism and promotes alterations in the metabolism of cellular free radicals in several organs such as the liver, kidneys, and heart [6][7][8][9][10]. Free radicals cause toxicity by attacking membrane phospholipids, leading to membrane injury through lipid peroxidation, depolarization of the mitochondrial membrane, and apoptosis [11].…”
Section: Introductionmentioning
confidence: 99%
“…Além disso, diversos trabalhos sugerem que o F pode interferir em muitas vias metabólicas, inibindo a ação de diversas enzimas e ainda atuando sobre a via glicolítica (DE LA SOTA et al, 1997;WHITFORD, 1996). Estudos realizados com animais experimentais, em laboratório, demonstraram que a ingestão aguda ou crônica de F pode alterar a expressão proteica em tecidos ósseo, hepático, renal, intestinal e dentário, bem como na urina de ratos ou camundongos (LEITE, 2010;KOBAYASHI et al, 2009;KOBAYASHI et al, 2011;KOBAYASHI, 2012;CARVALHO et al, 2013;PEREIRA et al, 2013;CHARONE et al, 2016;MELO et al, 2017;DIONIZIO et al, 2018 (VIÑALS et al, 1993;OTSUKI et al, 2005;ELLIOT et al, 2002;GOH et al, 2003;GUTIÉRREZ-SALINAS et al, 2010).…”
Section: Dose-response Effect Of Fluoride On Parameters Related To Inunclassified